2011
DOI: 10.1063/1.3581045
|View full text |Cite
|
Sign up to set email alerts
|

A flowing plasma model to describe drift waves in a cylindrical helicon discharge

Abstract: A two-fluid model developed originally to describe wave oscillations in the vacuum arc centrifuge, a cylindrical, rapidly rotating, low temperature and confined plasma column, is applied to interpret plasma oscillations in a RF generated linear magnetised plasma (WOMBAT), with similar density and field strength. Compared to typical centrifuge plasmas, WOMBAT plasmas have slower normalised rotation frequency, lower temperature and lower axial velocity. Despite these differences, the two-fluid model provides a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
(58 reference statements)
1
13
2
Order By: Relevance
“…As pointed earlier, the radial density gradient and accordingly edge density have an important effect on the non-resonant mode conversion of helicon wave into Trivelpiece-Gould wave and power absorption, we thereby choose these two density profiles with very different radial gradients. [20] The density level of 10 18 m −3 is also typical for helicon discharges [21,22,23,24,25]. All computed results are normalized to antenna current of 1 A, therefore, the presented power absorptions are relative results.…”
Section: Theoretical Model and Computational Schemementioning
confidence: 99%
“…As pointed earlier, the radial density gradient and accordingly edge density have an important effect on the non-resonant mode conversion of helicon wave into Trivelpiece-Gould wave and power absorption, we thereby choose these two density profiles with very different radial gradients. [20] The density level of 10 18 m −3 is also typical for helicon discharges [21,22,23,24,25]. All computed results are normalized to antenna current of 1 A, therefore, the presented power absorptions are relative results.…”
Section: Theoretical Model and Computational Schemementioning
confidence: 99%
“…Overall, the normalized frequency is lower on MEVAT for F > 0.4, which may be attributed to lower rotation frequency and ion temperature as revealed in a previous study. 18…”
Section: B Dispersion Relationmentioning
confidence: 99%
“…[7][8][9][10][11][12] Due to the nonuniform configurations of equilibrium magnetic field, discharge area and plume, plasma rotation driven by Lorentz force commonly occurs in various electric thrusters. [13][14][15][16] A few analytical models have been developed or/and applied to describe this flowing phenomenon, [17][18][19][20][21] but little attention was given to the resulted plasma instability which, however, can effect the propulsion efficiency, precise control, durable reliability and life time significantly. 22,23 This paper considers an emerging plasma propulsion technology, namely magnetically enhanced vacuum a) Electronic mail: leichang@scu.edu.cn arc thruster (MEVAT), [24][25][26][27][28] as an example and studies the instability evolution caused by plasma rotation and axial flow in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The bifurcation of these structures was also investigated in their model. Chang et al [243] applied a twofluid model to interpret plasma oscillations in the WOBAT device. They showed that the density and space potential profiles agreed with their experimental results, but the temperature profile was not flat in the observed results, as assumed by the model.…”
Section: Attempts For Self Consistent Modelmentioning
confidence: 99%